2003
DOI: 10.1121/1.1577556
|View full text |Cite
|
Sign up to set email alerts
|

The effect of speech presentation level on measurement of auditory acclimatization to amplified speech

Abstract: A systematic improvement in auditory performance over time, following a change in the acoustic information available to the listener (that cannot be attributed to task, procedural or training effects) is known as auditory acclimatization. However, there is conflicting evidence concerning the existence of auditory acclimatization; some studies show an improvement in performance over time while other studies show no change. In an attempt to resolve this conflict, speech recognition abilities of 16 subjects with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
78
1
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(90 citation statements)
references
References 32 publications
6
78
1
5
Order By: Relevance
“…The SPIN-test was presented to the hearing-impaired 438 subjects at constant noise levels above 80 dB SPL (see Table 1). Our results are in line 439 with those of Munro and Lutman (2003), who reported an acclimatization effect after 12 440 weeks of hearing-aid use, when using speech in noise at the highest presentation level 441 of 69 dB SPL, but only minimal for 55 and 62 dB SPL. Gatehouse (1989) also reported 442 that the aided ears performed better only at high presentation levels (>75 dB SPL), 443 while at lower presentation levels the unaided ear was advantaged.…”
Section: Latencies 296supporting
confidence: 91%
“…The SPIN-test was presented to the hearing-impaired 438 subjects at constant noise levels above 80 dB SPL (see Table 1). Our results are in line 439 with those of Munro and Lutman (2003), who reported an acclimatization effect after 12 440 weeks of hearing-aid use, when using speech in noise at the highest presentation level 441 of 69 dB SPL, but only minimal for 55 and 62 dB SPL. Gatehouse (1989) also reported 442 that the aided ears performed better only at high presentation levels (>75 dB SPL), 443 while at lower presentation levels the unaided ear was advantaged.…”
Section: Latencies 296supporting
confidence: 91%
“…However, baseline measures were not obtained immediately after fitting so it is impossible to ascertain from the data how much acclimatisation may have taken place within the initial six weeks of use. Previous research of acclimatisation to conventional hearing aids has shown that significant changes may take place in the initial six weeks post fitting (Gatehouse, 1992;Munro and Lutman, 2003). A further issue that may influence the validity of these results stems from the fact that there was no control group for the measurements taken after 6 months of frequency compression use.…”
Section: Auditory Acclimatisationmentioning
confidence: 75%
“…7 Auditory perceptual acclimatization is a systematic change in the auditory system with time. 18 There is an evident conflict about the existence of perceptual acclimatization, 19 as some studies have shown improved performance while other have failed to demonstrate the effects of auditory perceptual acclimatization. There are at least three explanations for the studies that did not find perceptual acclimatization.…”
Section: Discussionmentioning
confidence: 99%
“…22 Thirdly, findings may attempt to demonstrate perceptual acclimatization based on inappropriate levels in test materials, and thereby often fail. 19 Based on these statements, it is possible to question the effective use of hearing aids during our study period in adult and elderly subjects that showed no change in speech recognition with time. If about 50% of subjects showed improved SRTS and SRTN tests, then why did the other half show not changes or even worse results?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation